Harmony in Religious and Cultural Diversity: Case Study of Sungai Penuh City Society - Masnur Alam (Al-Albab, 2016)
This article was motivated by recent development in Indonesian society whose religious and cultural diversity has raised a lot of racial issues that lead to tension and suspicion among communities in the Sungai Penuh, Kerinci Regency, Jambi province on Sumatra Island. The impact could potentially trigger conflict, damage, inconvenience and could further threaten national unity and national integration. This article gives an overview that religion (Islam) has a very positive philosophy that in fact humans are created in religious and cultural diversity. Diversity is the law of God, something that is commonplace, rule of time, a must, and divine grace to be grateful for, a form generosity from God to humans as the strength, the reason to do good. The government together with the community has been able to build harmony in diversity, creating peace, moderation, compassion, love of peace, tolerance, avoiding conflict, so as to build the country as planned. In socializing the attitude of harmony, the government can do it through formal and non-formal ways, eventually people can implement it in their daily lives. Thus, the government and the public can establish harmony in diversity, creating peace, security, order, justice, tranquility, comfort as well as brotherhood and compassion. The government together with the community can come together, foster mutual cooperation to achieve the goals the country’s development. This paper also recommends to religious communities with diverse cultures to always build harmony as one of the solutions in creating peace and free from conflict, as well as serving as capital to build the country, nation, state and religion.